Rancang Bangun Smart Meter System untuk Penggunaan Air pada Rumah Tangga Berbasis Internet of Things - Ramdani Ramdani; I Gede Putu Wirarama Wedashwara W; Ariyan Zubaidi (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2020)
Water is one of the mineral resources which is a source of basic human needs and has many uses including drinking, bathing, washing and so on. In urban areas, clean water services are generally provided by the government through the PDAM (Regional Water Company). In the use of water, sometimes the user is not able to control the use of water which causes an enlarged water bill as in one of the houses in Pancor, East Lombok Regency. In this area, monitoring is still carried out conventionally by checking the water meter used. Monitoring systems are now widely used as an alternative way to monitor one of them in monitoring water use. In this study, a system (Smart Meter System) that can be used to control and monitor water usage in the household for more efficient water use is designed. By using WeMos as a microcontroller, Water Flow Sensor and MQTT (Message Queuing Telemetry Transport) protocol as data communication, remote control and monitoring of water use in households can be done in real-time.